1975
DOI: 10.1021/j100588a010
|View full text |Cite
|
Sign up to set email alerts
|

Small anion binding to cycloamylose. Equilibrium constants

Abstract: The equilibrium constants for the formation of inclusion complexes of a-and d-cycloamylose with small anions were measured using conductance methods. For the series of anions, C104-, SCN-, I-, Br-, and NO3-, the association constants for complexes with -cycloamylose are 28.9, 18.7, 12.4, 3.5, and 1.4 M-1. The association constant for SCN-with d-cycloamylose is 9.9 M-1. Cl-, SO42-, and acetate do not bind with a-cycloamylose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 0 publications
0
47
0
Order By: Relevance
“…This is most likely a reflection of the hydrophobic effect, which tends to squeeze DHA further into the hydrophobic HPβCD cavity as the S o for DHA decreases. The higher solubility of complexes prepared in acetate buffer than phosphate buffer at the same pH may be because phosphate buffer interferes with complexes of HPβCD and DHA, similar to sodium p-(4-hydroxy-1-naphthylazo) benzenesulfonate with β-CDs (Mochida et al, 1973); however, acetate ions do not interact with HPβCD (Wojcik and Rohrbach, 1975).…”
Section: Phase/equilibrium Solubilitymentioning
confidence: 99%
“…This is most likely a reflection of the hydrophobic effect, which tends to squeeze DHA further into the hydrophobic HPβCD cavity as the S o for DHA decreases. The higher solubility of complexes prepared in acetate buffer than phosphate buffer at the same pH may be because phosphate buffer interferes with complexes of HPβCD and DHA, similar to sodium p-(4-hydroxy-1-naphthylazo) benzenesulfonate with β-CDs (Mochida et al, 1973); however, acetate ions do not interact with HPβCD (Wojcik and Rohrbach, 1975).…”
Section: Phase/equilibrium Solubilitymentioning
confidence: 99%
“…This result is consistent with the D 1 mechanism, as identified by the TG and DTG analyses. It has been reported that the complexing process between cyclodextrins and guest molecules occurs at approximately the diffusion rate in solution [7]. The dissociation of [~-CD.CgI-IsO is dominated by a diffusion mechanism.…”
Section: Crystal Structure Analysismentioning
confidence: 99%
“…Preferable inclusion of Br -in comparison with Cl -, H 2 PO 4 -and SO 4 2-has been shown in our recent publication [20] as well as in the literature [21][22][23][24]. According to the NMR results [20,21], bromide is inserted into macrocyclic cavity and located near the inner protons H-5 of CDs.…”
Section: Resultsmentioning
confidence: 63%